2022
DOI: 10.37213/cjal.2022.32024
|View full text |Cite
|
Sign up to set email alerts
|

“French Teachers Can Figure It Out”: Understanding French as a Second Language (FSL) Teachers’ Work in the Context of the COVID-19 Pandemic

Abstract: In 2020, the coronavirus (COVID-19) pandemic forced teachers in Ontario to move online. Since then, teaching online or in hybrid models has been common across the province. To understand how French as a Second Language (FSL) teachers navigated these spaces, four Ontario French teachers were interviewed about their experience using educational technology and teaching online. Findings were analyzed in light of Hargreaves and Fullan’s (2020) reframing of classic understandings of teachers’ work in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although we acknowledge that sessional instructors can bring professional expertise and experience into the programs, stakeholders reported this has also limited opportunities for advocacy, stability, and consistency of the FSL specialization, and has diminished its perception within the larger ITE program. Such feelings of being overlooked are well-established in FSL literature (e.g., Knouzi & Mady, 2014;Smith & Arnott, 2021).…”
Section: Fsl Specialization Coursesmentioning
confidence: 90%
“…Although we acknowledge that sessional instructors can bring professional expertise and experience into the programs, stakeholders reported this has also limited opportunities for advocacy, stability, and consistency of the FSL specialization, and has diminished its perception within the larger ITE program. Such feelings of being overlooked are well-established in FSL literature (e.g., Knouzi & Mady, 2014;Smith & Arnott, 2021).…”
Section: Fsl Specialization Coursesmentioning
confidence: 90%
“…Arnott et al indicated at the time that "more research is needed to understand how the shift toward Web 2.0 technologies (that allow for interactivity and user creativity and communicative agency on the Web) have [sic] altered [or not] teachers' FLI [French language instruction]" (p. 74). In the context of the COVID-19 pandemic, Smith and Arnott (2022) confirm that "there are not yet studies exploring the delivery of FSL K-12 programming in an online or hybrid format resembling the virtual schooling situation of the .…”
mentioning
confidence: 90%
“…Although not representative of language teachers specifically, this study emphasized that students look to their teachers to help guide their uses of technology in the classroom, concluding that "teachers play a critical role in supporting self-regulated learning using technology and promoting positive impacts of technology for learning" (p. 86). A recent Ontario study carried out by Smith and Arnott (2022) highlighted FSL teachers' ongoing professional marginalization and seclusion, and their feelings of being disconnected from schools and boards. Indeed, study participants indicated that their technological competencies did not alleviate persistent challenges faced in the COVID-19 context.…”
Section: The Pivot To Online Teaching and Learning In Response To The...mentioning
confidence: 99%